764 Development of a new composite surface tensiometry parameter for quality evaluation of the maturation process of peloids by contact angle method (Balneo and PRM Research Journal, 2025)
With the introduction of the rheological and surface tensiometry approaches, peloids started to be viewed as a geological complex system that needed to be characterized in an integrated way. The development of the Rossi factor revealed variations in the surface free energy of Euganean thermal muds as a function of their quality, conformity, and matura-tion degree. The Rossi factor consents to measuring the contact angle of Fomblin HC/25PFPE Polyperfluoromethylisopropyl Ether by static sessile drop method. The de-velopment of the Kinetic Contact Angle sessile drop methodology, applied to the meas-urement of Fomblin HC/25 PFPE contact angles over time, led to the determination of an integrated surface tensiometry parameter for the evaluation of the maturation process of Euganean thermal peloids, here called the Maturation Mud Index. The Mud Maturation Index is based on the contact angle measurements performed onto peloids surfaces col-lected by Osservatorio Termale Permanente of University of Padova from 2005 to 2010. The Mud Maturation Index has shown a connection to the activity of thermal spas during their pelotherapy season. As a result, this index can serve as a valuable tool for surface tensiometry in assessing the maturation process quality of a peloid based on its level of maturation within the thermal activity of the Euganean Thermal Area in Padova, Italy.